Gastronomi dalam Tiga Cerita Pendek Rusia - Gustav Gallenius; Mochamad Aviandy (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
This study aims to analyze gluttonny shown in three short-stories by Anton Chekhov through the behaviour and action of the characters towards cuisine. The three short-stories are Сирена (Sirena), Oysters (Ustritsy), and Silly Frenchman (Gluppy Frantsuz). This study uses descriptive analysis method by analyzing the quotations in the short-stories. Through gastronomic literature approach within analyzing this research, it can be concluded that gluttony arises from poshlost and the carnal apettite inside human beings. In addition, character acted as catallisator of gluttony existed in order to create temporary pleasure for the characters as they enjoy their food and ultimately falling into the gluttonous bottomless pit.Keywords - Gastronomy, Gluttony, Poshlost, , Russia, Short-story.